Pterosaurs of the Wessex Formation (Early Cretaceous, Barremian) of the Isle of Wight, southern England: a review with new data - Sweetman, S. C.; Martill, D. M. (Journal of Iberian Geology, 2010)
Micropalaeontological processing of vertebrate-bearing horizons within the Early Cretaceous (Barremian) Wessex Formation of the Isle of Wight, southern England, reveals a rare, but diverse assemblage of pterosaurs. Besides the previously known euornithocheiran Caulkicephalus, the new material demonstrates the presence of three species of istiodactylid, a ctenochasmatid, and a distinct form that cannot easily be placed in a higher taxon. This elevated diversity is in keeping with pterosaur diversity from other Early Cretaceous localities, having some similarities with assemblages from the Early Cretaceous of Brazil, China and Spain. The apparent absence of toothless forms in the Wessex Formation may represent a preservation bias or collecting artefact.